ANCAMAN PEMBERATAN PADA JENIS HUKUMAN DISIPLIN MILITER SEBAGAI UPAYA PENCEGAHAN PELANGGARAN DISIPLIN PRAJURIT TENTARA NASIONAL INDONESIA (TNI) - Nurdin Nurdin (Legal Spirit, 2019)
This study aims to analyze the regulation of the threat of punishment for military discipline as regulated in Article 11 of Law Number 25 of 2014 concerning Military Disciplinary Law and to find out juridical problems faced by superiors who have the right to punish (Ankum) in the application of Law Number 25 of 2014 concerning Military Discipline Law. In the discussion of this research, the juridical problems faced by Ankum usually have a tug of war between Ankum and law enforcement authorities (civilians). When warriors commit violations related to civilians, then it is usually difficult for Ankum to take action. From this aspecttoo, Ankum usually felt that his position as Commander felt failed because of violations committed by his subordinates. Furthermore, the application of sanctions given by Ankum to soldiers who were sentenced to military discipline had a deterrent effect on the perpetrators, this proved to be fewer violations every year